(untitled) (TEST Ticontre. Theory Text Translation, 2022)
At the end of 1913, the Moscow-based Futurist group Mezzanine of Poetry (Mezonin Poėzii) published the almanac Krematorij Zdravomyslija [The Crematorium of the Common Sense]. The almanac came out right before the group separated and thus represents its legacy. Gathering the works of fourteen poets of the Mezzanine, this voluminous publication stands out for its attempt – set down by the two theoretical leaders of the group: Vadim Šeršenevič (1893-1942) and Lev Zak (1892-1980, who signed his works as Chrisanf and as M. Rossijanskij) – to shape a genre of experimental prose that would reflect the vividness and innovation of the poetic language of Russian Futurism. The present paper analyses the stylistic features of three prose works in the almanac: two excerpts from Šeršenevič’s unfinished novel Introdukcija samoubijcy [The Suicide’s Prelude] and L. Zak’s short story Knjažna Karakaticeva [Princess Cuttlefish]. It does so in reference to Marinetti’s statements and to Šeršenevič and Zak’s theoretical writings on prose, included in the same almanac. Prose is one of the least investigated literary forms in Futurism Studies. Thus, the analysis deals mostly with primary sources and with the documents collected by V. Markov and V.P. Lapšin. The aim is to shed light on the continuity in the development of Italian and Russian Futurist experimental prose and, specifically, to read the works of Šeršenevič and Zak from a new comparative perspective, investigating the extent to which they used the theoretical principles set down by Italian Futurism.